Impact of different land uses on soil organic carbon stock in Karbi Anglong district of Assam, India - KALITA, NILIM; DUTTA, SAMIRAN; DAS, KULENDRA NATH; KURMI, KHAGEN; PATGIRI, DILIP KR. (Journal of Soil and Water Conservation, 2023)
The conversion of native ecosystems, such as forests to other land uses is known to have adverse impact on soil properties and loss of soil organic carbon (SOC), but no information is available on the magnitude of SOC storage and its dynamics under various prevailing land uses in the hill zone of Assam, India. The major objective of this study was to estimate SOC storage and status over time due to conversion of forest to different land-use systems, viz. shifting cultivation (Jhum), Rubber plantation, Crop land, Homestead garden, and Bamboo plantation in Karbi Anglong district which covers a major part of the hill region of Assam. Relative to forest land, SOC contents in the surface soils of Jhum land, rubber plantation, crop land, home garden and bamboo plantation system depleted by 50.84%, 30.51%, 52.54%, 20.33% and 20.33% respectively. The profile weighted mean values of SOC concentration was in the order: Forest> Homestead garden > Rubber plantation >Bamboo plantation >Jhum land>crop land with mean values of 0.77, 0.66, 0.62, 0.57, 0.51 and 0.42 per cent, respectively. The total SOC stock in the profile (0-50cm) followed the order - Forest > Homestead garden > Rubber plantation > Jhum land>Bamboo plantation> crop land with the total SOC Stock in each land use being 44.23 Mg C ha-1, 40.94 Mg C ha-1, 39.31 Mg C ha-1, 32.63 Mg C ha-1, 32.34 Mg C ha-1 and 27.54 Mg C ha-1 respectively. The soils of crop land recorded the highest depletion of SOC stock (37.7%) followed by jhum land (26.2%) due to shifting from natural forest. The significant positive correlation of SOC stock and water stable aggregates indicated that soils under forest land and tree based land uses have greater potential to sequester SOC than those in the cropland soils due to increased soil aggregate stability.